PATTERNS OF HORMONE REPLACEMENT THERAPY USE AND ITS EFFECT ON MENOPAUSAL SYMPTOMS AND METABOLIC PROFILE IN POSTMENOPAUSAL WOMEN: A PROSPECTIVE CLINICAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Menopause is a natural biological transition in a woman’s life associated with declining estrogen levels, leading to a wide range of vasomotor, psychological, and metabolic disturbances. Hormone Replacement Therapy (HRT) is widely used for the management of menopausal symptoms, but its usage patterns and metabolic effects vary among populations. Aims and Objectives: To assess the pattern of Hormone Replacement Therapy (HRT) use and its effect on menopausal symptoms and metabolic profile in postmenopausal women, including evaluation of symptom relief and changes in metabolic parameters among HRT users compared to non-users. Materials and Methods: This prospective hospital-based observational study was conducted in the Department of Obstetrics and Gynaecology, Deben Mahato Govt Medical College (MS) over 18 months. A total of 120 postmenopausal women attending the outpatient department were included and divided into HRT users and non-users. Clinical data, menopausal symptoms, and metabolic parameters were assessed and compared between groups. Results: Age distribution was similar in both groups (p = 0.68). Estrogen + progesterone was the most common HRT (63.3%). HRT users had significantly lower vasomotor scores (p < 0.001) and showed improved lipid profile, glycemic status, BMI, and blood pressure compared to non-users (p = 0.04 to